MECHANISMS FOR IMPROVING THE METHODOLOGY OF TEACHING A FOREIGN LANGUAGE IN SECONDARY SCHOOLS (World Bulletin of Social Sciences, 2025)
This article analyzes mechanisms for improving foreign language teaching methodology in general education schools. The paper examines the importance of modern approaches, innovative methods and technologies, teacher professional development issues, and ways to improve curricula. Based on literature analysis, practical recommendations for improving foreign language teaching methodology have been developed